Anopheles stephensi Heme Peroxidase HPX15 Suppresses Midgut Immunity to Support Plasmodium Development - Kajla, Mithilesh; Kakani, Parik; Choudhury, Tania Pal; Kumar, Vikas; Gupta, Kuldeep; Dhawan, Rini; Gupta, Lalita; Kumar, Sanjeev (Frontiers in Immunology, 2017)
The heme peroxidase HPX15 is an evolutionary conserved anopheline lineage-specific gene. Previously we found that this gene is present in the genome of nineteen worldwide distributed different species of Anopheles mosquito and its orthologs are absent in other mosquitoes, insects or human. In addition, 65-99% amino acid identity among these 19 orthologs permitted us to hypothesize that the functional aspects of this gene might be also conserved in different anophelines. In this study, we found that Anopheles stephensi AsHPX15 gene is mainly expressed in the midgut and highly induced after uninfected or Plasmodium berghei infected blood feeding. RNA interference (RNAi)-mediated silencing of midgut AsHPX15 gene drastically reduced the number of developing P. berghei oocysts. An antiplasmodial gene nitric oxide synthase (NOS) was induced thirteen fold in silenced midguts when compared to the unsilenced controls. Interestingly, the induction of antiplasmodial immunity in AsHPX15 silenced midguts is in absolute agreement with A. gambiae. In A. gambiae, AgHPX15 catalyzes the formation of a dityrosine network at luminal side of the midgut that suppresses the activation of mosquito immunity against the bolus bacteria. Thus, a low immunity zone created by this mechanism indirectly supports Plasmodium development inside the midgut lumen. These indistinguishable functional behaviors and conserved homology indicates that HPX15 might be a potent target to manipulate the antiplasmodial immunity of the anopheline midgut and it will open new frontiers in the field of malaria control.